2005
DOI: 10.17221/5650-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite influence on fish: a review

Abstract: ABSTRACT:Nitrite is an intermediate in the oxidation of ammonium to nitrate. An elevated ambient nitrite concentration is a potential problem for freshwater fish since nitrite is actively taken up across the gills in competition with chloride. Nitrite is a well-known toxicant for fish as well as a disrupter of multiple physiological functions including ion regulatory, respiratory, cardiovascular, endocrine and excretory processes. One critical consequence of nitrite accumulation is the oxidation of haemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
124
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(134 citation statements)
references
References 74 publications
3
124
0
7
Order By: Relevance
“…Nitrite diffuses from the blood plasma into red blood cells, where it oxidises the Fe 2+ in haemoglobin (Hb) to the Fe 3+ oxidation state, converting haemoglobin into methaemoglobin (metHb). MetHb reduces the total oxygen-carrying capacity of the blood [16]. Nitrite exposure resulted in a reduction in haemoglobin and haematocrit in tilapia (Oreochromis niloticus) with mild methaemoglobinaemia following exposure to 0.50 and 1.38 mg·L −1 NO 2 − -N for 48-h static tests [17].…”
Section: Water Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrite diffuses from the blood plasma into red blood cells, where it oxidises the Fe 2+ in haemoglobin (Hb) to the Fe 3+ oxidation state, converting haemoglobin into methaemoglobin (metHb). MetHb reduces the total oxygen-carrying capacity of the blood [16]. Nitrite exposure resulted in a reduction in haemoglobin and haematocrit in tilapia (Oreochromis niloticus) with mild methaemoglobinaemia following exposure to 0.50 and 1.38 mg·L −1 NO 2 − -N for 48-h static tests [17].…”
Section: Water Qualitymentioning
confidence: 99%
“…Because nitrite affects the ability of blood to transport oxygen, a reduction in ambient water DO concentrations increases the effect of toxicity. Although there are many studies about acute and sublethal effects of nitrite on fish in the literature [14,16,[20][21][22], comprehensive studies on the chronic effects of nitrite on different fish species under aquaponic conditions will be necessary considering the interaction of plant roots and the efficiency of related bacteria in the system. In brief, the related bacteria that may be involved in aquaponic systems are the following: ammonia-oxidizing bacteria (AOB), including bacteria of the genera Nitrosomonas, Nitrosococcus, Nitrosospira, Nitrosolobus, and Nitrosovibrio, and nitrite-oxidizing bacteria (NOB), including bacteria of the genera Nitrobacter, Nitrococcus, Nitrospira, and Nitrospina [23].…”
Section: Water Qualitymentioning
confidence: 99%
“…Apart from methaemoglobinaemia, studies on fish and crustaceans have revealed that nitrite is a disrupter of a large variety of physiological functions, including ion regulatory, respiratory, endocrine and excretory processes (Jensen, 2003;Kroupova et al, 2005).…”
mentioning
confidence: 99%
“…In general, the most important source of human exposure to nitrate and nitrite is through vegetables (nitrite and nitrate) and through meat in the diet. In some circumstances, however, drinking water can make a significant contribution to nitrate and, occasionally, nitrite intake (Kroupova et al 2005). In the case of bottle-fed infants, drinking-water can be the major external source of exposure to nitrate and nitrite.…”
Section: Physico-chemical Examinationmentioning
confidence: 99%